(untitled) (Comparatismi, 2023)
Nostalgia is an emotion that binds a memory to an emotional component, divided between melancholy and comfort. In comics, nostalgia can be elicited through several thematic, formal, and structural triggers. McGuire’s Here (2014) is a peculiar example of these dynamics. Through a non-chronological, fragmentary progression, the graphic novel tells several mundane moments of millions of years of a corner of the United States, seen from a fixed perspective and occupied mainly by a living room. Here thus shows, on first analysis, a scattered and frayed plot, which implies low narrativity and should result in an anti-nostalgic attitude. However, these effects are countered by an antithetical set of mechanisms that ask to imbue the transitions between panels with meaning and reconstitute the textual network of semantic and plastic echoes, encouraging active reading and producing ambivalent effects for the nostalgic feeling.